Blown away [large type] - Sala, Sharon (Sala, Sharon. Storm front novel, 2010)
Writer Cari North thought she knew all there was to know about plot twists--until she stumbled across her ex-fiancé, Lance Morgan, digging a shallow grave in the Louisiana woods. After one horrifying moment of shared recognition, Cari knew her life hinged upon whether she could outrun Lance and the hurricane-spawned tornado that was barreling down on their heels. Just when she thinks she's lost Lance and heads for home, the storm throws in yet another twist that will change her fate--forever.